"Comparative Study in Certain Aspects of Muscular Strengths of Lower and Upper Body Extremes Among Shot Put, Discus, and Javelins Thrower" (Journal of the College of Basic Education, 2022)
The sport of the handicapped is one of the most important private sports nowadays because it plays a major role in the rehabilitation of persons with disabilities to achieve high achievements and to raise their countries' names in international forums. And to enrich their lives in the full sense ", in addition to serving humanity and restoring self-confidence among persons with disabilities and providing them with the opportunity to practice various sports as equals. He thought of a polo wheelchair competition and followed it with a more appropriate idea for the disabled. The success of the therapeutic exercise of disabled people and their spread to start a global sports movement for the disabled paralyzed, Due to the specificity of the conditions taken by the object of the disabled player in this activity, which requires him to agree with the mechanical conditions in the performance of their skills, especially the effectiveness of throwing, and the lack of specialized studies that confirm this during the training of this special category and through follow-up field researcher and meet the trainers, In the performance of some exercises for the effectiveness of throwing the weight of the disabled, and may be the cause of physical or mechanical, which prompted the researcher to study this situation and the design of a training program to them according to mechanical conditions to develop the level of performance of the effectiveness of throwing the weight of the disabled from sitting. The choice of the correct scientific method must be consistent with the problem to be studied. Since the nature of the problem that the researcher wants to study, he must use the experimental method after him. "The most efficient means of reaching a reliable knowledge". The study sample was chosen in a deliberate manner, and consisted of players from the Iraqi national team in the handicap games of the disabled from the seating position of 6 players. The researcher took into consideration the degrees of handicap in between them by presenting the computational circles and standard deviations in explanatory tables after conducting tribal and remote statistical operations through analysis And to explain the reality of the differences and their statistical significance. Conclusions and recommendations;1. Dependence on the results of kinetic analysis has contributed to the diagnosis of individual performance for each disability category.There appears to be a random correlation between mechanical variables, speed, maximum force and starting point.The need to take care of modern training and the use of advanced means and devices to reach the best level of achievement in throwing activities.The need to use advanced imaging equipment through training in order to obtain the best angles of the situation of each of the activities of throwing.The study aims at being acquainted with the significances of muscular strengths aspects (maximum, power, and explosive) of lower and upper body extremes among shot put, discus, and Javalin Thrower. The ample consists of a athletes representing the advanced Ninavah team in throwing activities. The sample divided into 3 athletes each activity. The equality had done among the Hwee types of Hwrowers in vanables of age, high, and muscular mass. The Maximum, power, and explosive strengths for upper body extreme were measured by test of plans beush press. The same aspects of muscular strengths for lower body extreme were measured by test of full legs bending. The intensities of tests were determined by analyzing the content of scientific Resources. The data were processed statically by using Mean, standard deviation, percentage, Anova, and LSD. The researcher then concluded the following: The shot putter excelled in Maximum strengths of upper and lower body extremes, followed by discus then Javelin Throws.The shot discus excelled in Maximum strengths of upper and lower body extremes, followed by Javelin Throws then shot putter.The shot pusher excelled in explosive strength of upper body extreme followed by discus then javelin throwers.the javelin throwers excelled in explosive strength of lower body extreme followed by discus throwers then shot putter.